PKM Introduksi Vegetasi Tanaman Pakan Lebah dan Potensi Budidaya Lebah Tanpa Sengat (Galo-Galo) di Jorong Rimbo Janduang, Nagari Lingkuang Aua, Kecamatan Pasaman, Kabupaten Pasaman Barat - Simel Sowmen; Rusdimansyah Rusdimansyah; Imana Martaguri; Qurrata Aini; Mardhiyetti Mardhiyetti; Riesi Sriagtula (Warta Pengabdian Andalas, 2022)
Jorong Rimbo Janduang is located in Nagari Lingkuang Aua, Pasaman District, West Pasaman Regency. The main livelihoods of the local people are gardeners and traders. There are many types of plant vegetation in Jorong Rimbo Janduang, some of which can be the main source of food for bees, but the community around the location has not cultivated stingless bees (galo-galo). Raising gallo-galo is different from raising cows, goats, and chickens because we do not need to look for food every day, as long as there are lots of bee-feeding plants growing around it. The success of gallo-galo cultivation is 70-80% influenced by the availability of feed sources in the form of nectar, pollen, and resin obtained from forage plant vegetation around the cultivation site. This community engagement activity aims to increase the knowledge and the desire of the community for stingless bee farming, increase the vegetation of forage plants around the location for beekeeping, and improve the community's economy. The methods used were counseling, mentoring, training, and modeling. The method of implementing science and technology is carried out by applying several technologies according to the objectives of these social services.